The development of animated videos for teaching refusal speech act - Rika Rahim; Indah Tri Purwanti; Afrianto Daud (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
This study explores the development of animated videos for teaching refusal speech acts. It employs a Research and Development (R&D) design using the ADDIE model, limited to the Analysis, Design, and Development stages (Sugiyono, 2016). The research was carried out at the English Study Program of Universitas Riau during the 2023/2024 academic year. The participants included 39 students as research subjects and three expert validators representing media, material, and teaching expertise. Data were gathered through need analysis interview and questionnaires. The results revealed that students exhibited a strong preference for animated videos (84.6%) compared to conventional media. Lecturer’s interview showed that animated videos were needed to increase engagement and support students’ understanding of refusal expressions in diverse contexts. Validation results from experts indicated that the developed videos were rated as “very valid”, with average scores of 4.31 out of 4 for media design, 4.56 out of 4 for pedagogical aspects, and 4.95 out of 4 for material quality. Students’ responses further supported the feasibility of the videos, with average score of 80.19% for video 1, 80.06% for video 2, categorized as “feasible”, and 81.48% for video 3, categorized as “very feasible”. Overall, the findings suggest that animated videos serve as a very valid and feasible instructional medium for enhancing students’ pragmatic competence, particularly in refusal speech acts. These results also underscore the potential of animated videos media as valuable educational resources for teaching refusal speech act.